2009
DOI: 10.1080/00365510902770061
|View full text |Cite
|
Sign up to set email alerts
|

Patients referred to an indoor air health clinic: exposure to water-damaged buildings causes an increase of lymphocytes in bronchoalveolar lavage and a decrease of CD19 leucocytes in peripheral blood

Abstract: Confirmed exposure to water damage was associated with an increase in symptoms. Exposure to water damage caused a significant change in the cellular composition in BAL fluid (lymphocytosis) and blood (decrease of CD19 cells). The depletion of CD19 leucocytes in peripheral blood may indicate an active immune response in the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…There is currently no well-defined diagnostic criteria for the great majority of DBRI:s. The symptoms tend to be quite diverse but include fever, myalgias, cough and headaches somewhat reminiscent of PM. Recently we have shown that exposure to water damage in buildings is associated with an increase in lymphocytes in BAL, this is similar to findings in HP and some cases of pulmonary mycotoxicosis, although the there was no change in the CD4/CD8 ratio in contrast to the increase of CD8 cells usually seen in HP 43. In this study the number of macrophages was also increased but the increase was not significant possibly because of a lag between the start of symptoms and the BAL procedure.…”
Section: Inflammatory Diseases In the Airways Caused By Exposure To Msupporting
confidence: 85%
See 1 more Smart Citation
“…There is currently no well-defined diagnostic criteria for the great majority of DBRI:s. The symptoms tend to be quite diverse but include fever, myalgias, cough and headaches somewhat reminiscent of PM. Recently we have shown that exposure to water damage in buildings is associated with an increase in lymphocytes in BAL, this is similar to findings in HP and some cases of pulmonary mycotoxicosis, although the there was no change in the CD4/CD8 ratio in contrast to the increase of CD8 cells usually seen in HP 43. In this study the number of macrophages was also increased but the increase was not significant possibly because of a lag between the start of symptoms and the BAL procedure.…”
Section: Inflammatory Diseases In the Airways Caused By Exposure To Msupporting
confidence: 85%
“…In this context it is of interest that in cases of HP in agricultural settings, symptomless persons also exposed to the dust in question have increased levels of lymphocytes in their BAL fluid, as do people exposed to water damaged buildings 43. To some extent DBRI can perhaps be considered to be related to HP with some cases including features of pulmonary mycotoxicosis.…”
Section: Discussionmentioning
confidence: 99%
“…We have earlier shown that DBRI is associated with a lymphocytosis in BAL fluid [16]. In this study the relative lack of protein changes in DBRI, although lymphocytosis was present, can be seen to be in parallel with an earlier report where no HP ensued in asymptomatic dairy farmers although they demonstrated increased BAL lymphocyte levels because of exposure to moldy hay [34].…”
Section: Discussionsupporting
confidence: 88%
“…Thus the proteomic analysis suggests that the DBRI, at least its usual clinical presentation, is distinct from HP and HP-like conditions. However, it is possible that the proteomic pattern in an initial phase of DBRI display more similarities with HP and AME, in addition the exposure to damp buildings can sometimes cause clinical HP [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation